Early Holocene occurrence of thermophilous trees in the Storulvån valley - Andersson, Daniella (2008)
Recent studies on vegetation history in the Swedish Scandes have altered the view on deglaciation and patterns of vegetation colonization. It is now suggested that the mountains were deglaciated earlier than previously thought and the climate being warm enough to allow thermophilous tree species to establish further north than generally thought. Macrofossil finds from the area around Storulvån in western Sweden confirm that Ulmus glabra, Quercus robur and Corylus avellana have been present during the early Holocene. The aim of the study is to evaluate occurrences of pollen from thermophilous deciduous tree species in pollen diagrams from the Storulvån area in the southern Scandes where macrofossils from these species have been found and dated. A mire close to the macrofossil site on the southern slope of Mt. Getryggen was selected for the study and two parallel cores were taken for pollen analysis. The results showed recordings of Quercus, Tilia, Ulmus and Corylus, mainly between 7500 and 2800 calibrated years before present. The thermophilous tree species have grown in this area on their distributional limits and their pollen productivity has most likely been reduced if not occasionally even impaired. So general lowest pollen percentage limits that have been sometimes used as an indication of local presence must be treated with care, and validation of local presence must be done by other means and through comparison with similar studies and macrofossils. The present results were compared to similar pollen studies performed in the area and the results suggest that here the low pollen shares of Quercus, Tilia, Ulmus and Corylus, are in fact local imprints that can be interpreted as originating from trees that grew in the study area. It can be concluded that Quercus, Tilia, Corylus and possibly Ulmus most likely have been present on the prosperous south-facing slope during periods of favourable climate.